Optimisme sebagai Mediator hubungan Self-Compassion dengan Subjective Well-Being pada Santri MA di Pondok Pesantren Khairul Ummah - Gustiwi, Triska; Rajab, Khairunnas; Khairi, Zuriatul; Anwar, Khairil (Universitas Brawijaya, 2024)
Students personal development must be taken into account, students have the right to subjective well-being or feelings of pleasure, worth, life satisfaction and their status as students in Islamic boarding schools. This study aims to determine contribution of gratitude to the subjective well-being senior high school students Khairul Ummah Islamic Boarding School. The sample was selected by using proportioned stratitified random sampling where the sample was Islamic senior high school students at the Khairul Ummah Islamic Boarding School, with 193 students. Data collections used a subjective well-being scale that was made by the researcher based on the aspects proposed by Tian (2008), a self-compassion scale Neff (2003) and the optimism scale (lot-r) By (Scheir, Charles, & Bridges, 1994) which was developed by Suryadi, et al (2021).Simple linear regression and the PROCESS Macro Hayes 4.2 of SPSS 22.0 were used for data analysis. The result of study indicated that there is a partial mediation of optimism as a mediator between self-compassion and subjective well-being in students. Keywords: Subjective Well-Being, Self-Compassion, Optimism, Mediator Test